Screening Of Paper Industry Effluent For Heavy Metal Absorbing Bacteria - SATPAL SINGH BISHT,; B.PRAVEEN,; M. RUKMINI, (International Journal of Pharma and Bio Sciences, 2012)
The present study was conceptualized to evaluate the heavy metal absorbing potential of microbes isolated from paper industry effluent. The effluent was used as the source sample, after screening morpho-metrically ten strains were cultured and sub cultured to achieve the pure discrete colonies. Out of ten discrete colonies two were found to have the heavy metal absorbing ability. These two bacteria were identified as Bacillus cereus and Corynbacterium xerosis respectively. The heavy metal tolerant efficiency was determined by analyzing the growth of the bacteria in presence of heavy metal (Cu,Hg,Co and Zn) solution and their optimum tolerance was determined by measuring the optical density at 600nm after 24hr and 48hr of incubation. Bacillus cereus and Corynbacterium xerosis were both observed as heavy metal tolerant bacteria further these two microbes were subjected to sensitivity testing against commercially available antibiotics.